Severe Leptospira interrogans serovar Icterohaemorrhagiae infection with hepato‐renal‐pulmonary involvement treated with corticosteroids. Issue 5 (15th September 2014) - Schulze, Marco H.; Raschel, Heribert; Langen, Heinz‐Jakob; Stich, August; Tappe, Dennis
Abstract : The traditional concept of immediate antibiotic treatment in suspected leptospirosis seems to be especially important for patients up to day 4 of clinical illness. As immune mechanisms probably play a crucial role in advanced leptospirosis with presumed pulmonary hemorrhages, patients might benefit from corticosteroids or other immunosuppressive agents beside antibiotics. Key Clinical Message: The traditional concept of immediate antibiotic treatment in suspected leptospirosis seems to be especially important for patients up to day 4 of clinical illness. As immune mechanisms probably play a crucial role in advanced leptospirosis with presumed pulmonary hemorrhages, patients might benefit from corticosteroids or other immunosuppressive agents beside antibiotics.